2022
DOI: 10.3389/fcvm.2022.982871
|View full text |Cite
|
Sign up to set email alerts
|

The impact of myocardial fibrosis biomarkers in a heart failure population with atrial fibrillation—The HARVEST-Malmö study

Abstract: BackgroundSeveral studies suggest that circulating biomarkers of myocardial fibrosis are associated with worse prognosis in subjects with atrial fibrillation (AF). Here, we aimed to explore associations between fibrosis biomarkers, prevalent AF, and left atrial volume (LAV) enlargement in subjects with heart failure (HF). Additionally, we evaluated the prognostic impact of fibrotic biomarkers in HF with co-existing AF.Materials and methodsPatients hospitalized for HF (n = 316, mean age 75 years; 30% women) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A total of 12 studies were analyzed with 11,961 participants (including 1,707 AF patients and 10,254 controls). The pooled analysis of 10 studies ( 12 , 21 , 24 , 25 , 27 , 28 , 32 , 34 , 36 , 37 ) as a continuous variable indicated that sST2 was associated with the risk of AF occurrence (HR:1.04, 95% CI: 1.02–1.07, P < 0.01; I 2 = 67.8% Figure 2 ). Sensitivity analyses showed that the outcomes were stable ( Supplementary Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 12 studies were analyzed with 11,961 participants (including 1,707 AF patients and 10,254 controls). The pooled analysis of 10 studies ( 12 , 21 , 24 , 25 , 27 , 28 , 32 , 34 , 36 , 37 ) as a continuous variable indicated that sST2 was associated with the risk of AF occurrence (HR:1.04, 95% CI: 1.02–1.07, P < 0.01; I 2 = 67.8% Figure 2 ). Sensitivity analyses showed that the outcomes were stable ( Supplementary Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full text, 14 studies were further excluded because 3 were reviews, 5 were irrelevant findings, and the other 6 were inadequate data. Finally, 24 studies ( 12 14 , 17 37 ) were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations